(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Anggorojati A, Widayat R, Budi S. 2023. Visualization of paddy in Panel 65 of the Karmawibhangga Section of Borobudur Temple. Biodiversitas 24: 990-1003. Borobudur Temple is a building whose reliefs depict the Buddhist scriptures in the form of pictures, reliefs, and statues. Each relief contains a certain message and interpretation that not all visitors can understand the storyline when they observe, especially only at a glance. The Karmawibhangga relief is found at the Borobudur Temple’s lowest section. The lowest relief represents the hustle and bustle of worldly life, consisting of 160 panels, all of which have different images from one panel to another. Based on the existing literature results, an iconographic approach, reliefs in the form of paddy, is used to analyze the interpretation of the Karmawibhangga relief 65 on paddy to make it easier for people who desire to acquire information about it to symbolize prosperity. Paddy is depicted with plump grains, ready to harvest and being guarded by several people from rats. This study can be used as a reference in the future regarding the visualization description of paddy in the Karmawibhangga relief for future researchers.